2022
DOI: 10.3389/fnbeh.2022.901425
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic action of ayahuasca in a non-human primate model of depressive-like behavior

Abstract: Observational studies of long-term users of ayahuasca, an Amazonian psychedelic brew, suggest an increase in resilience via improvements in emotion and cognition. Ayahuasca has also demonstrated clinical antidepressant effects in human and animal studies; however, its potential prophylactic action in depression has not been previously studied. Therefore, this experimental study sought to evaluate the potential prophylactic effects of repeated and long-term ayahuasca use, via the modulation of resilience, in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…For instance, in the case of the present study, regular users of hallucinogenic drugs also showed an enhanced detachment from the information given by politicians and the media, which has been repeatedly related to higher distress scores during the initial waves of the pandemic 79 , 80 . Remarkably, a recently published preclinical study suggested that the use of ayahuasca could have a prophylactic effect in front of depressive symptoms 81 . Thus, a similar mechanism might be responsible for the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of the present study, regular users of hallucinogenic drugs also showed an enhanced detachment from the information given by politicians and the media, which has been repeatedly related to higher distress scores during the initial waves of the pandemic 79 , 80 . Remarkably, a recently published preclinical study suggested that the use of ayahuasca could have a prophylactic effect in front of depressive symptoms 81 . Thus, a similar mechanism might be responsible for the present findings.…”
Section: Discussionmentioning
confidence: 99%